The 1992 Struggle for Design and Technology - Wright, Ruth (Design and Technology Education: An International Journal, 2008)
This article seeks to illustrate that there is a need to collectively agree on the key purposes, nature, and value of design and technology. Transcribed press cuttings of the period are used to support this premise and also illustrate that D&T policy can be formed and challenged by people, not disembodied actors, on the outside of government policy-making machinery. In exploring a case of a policyforming struggle it purposefully utilises a practice (what real people do) and narrative approach. Following a general introduction, including dimensions of research in policy fields, some other aspects of context – at theoretical and practice level – are discussed before moving to a story of a 1992-3 press debacle in England over the nature of D&T. A brief early diversion from the story provides further contextual background to one of the key protagonists in the 1992 debate – the Engineering Council. The paper then offers some further thoughts before proposing that there needs to be a renewed attempt at exploring the well-foundedness of policies relating to design and technology, discussing positions on a range of D&T matters, and establishing a collectively agreed, explicit, and internally consistent policy position for design and technology.